Analisis Kesenjangan Kualitas Pelayanan berdasarkan Kepuasan Pasien Poliklinik Saraf RS Bhayangkara Surabaya - Luh Wayan Ema Natarini (Universitas Airlangga, 2018)
Background: Neurological polyclinic service at Bhayangkara Hospital in Surabaya is one of polyclinics that has an increasing number of patient visits every year. To keep patients’ loyalty towards a neurological polyclinic, the hospital must be able to meet patients’ needs so that patients feel satisfied.Aims: Therefore, it is necessary to conduct an assessment related to expectations and real service obtained by patients at the neurological polyclinic. The purpose of this study is to analyze the gap on the service quality and satisfaction level based on expectations and real service quality.Method: The study design was cross sectional with 50 respondents as the sample taken by simple random sampling. The research method was a survey as a questionnaire instrument.Results: The result showed that the satisfaction level of respondents in neurological polyclinic in general was very satisfying. The gap value of the overall research is that the service quality at the neuropathic polyclinics has a negative gap (-0.06). The service quality has not met patients’ expectations.Conclusion: In conclusion, the service quality is a vital part in Bhayangkara Hospital, Surabaya. The hospital can maintain their good image and patient visit if the service quality is excellent too. The hospital should improve the waiting room convenience and the discipline of their staffs to create better service quality.Keywords: patients’ satisfaction, gap analysis, quality dimension, service quality